Implementasi Kegiatan Esktrakurikuler English Club Dalam Mengembangkan Keterampilan Berbahasa Inggris - Lusiyana Suherman, Hana; Danang Dwi Basuki; Fitri Yessi Jami (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
Extracurricular English Club is an activity held by the school to add English lessons to English Club extracurricular activities. To develop English language skills in Learners. It is also driven by the interest and talent of learners in English. Extracurricular activities become a place for students to channel their interests and talents. This study aims to determine the process of implementing English Club extracurricular activities in developing English language skills as well as supporting and inhibiting factors. This research uses descriptive research method with qualitative approach. The informants in this study were teachers who support English Club extracurricular activities and students who participated in English Club extracurriculars. The data collection techniques used are observation, interviews, and documentation. The steps in analyzing data are using data collection techniques, data reduction, data presentation, and conclusion making.